No evidence of direct association between GLUT4 and glycogen in human skeletal muscle. Issue 22 (22nd November 2018) - Murphy, Robyn M.; Flores‐Opazo, Marcelo; Frankish, Barnaby P.; Garnham, Andrew; Stapleton, David; Hargreaves, Mark
Abstract: Previous studies have demonstrated that exercise increases whole body and skeletal muscle insulin sensitivity that is linked with increased GLUT4 at the plasma membrane following insulin stimulation and associated with muscle glycogen depletion. To assess the potential direct association between muscle glycogen and GLUT4, seven untrained, male subjects exercised for 60 min at ~75% V O2 peak, with muscle samples obtained by percutaneous needle biopsy immediately before and after exercise. Exercise reduced muscle glycogen content by ~43%. An ultracentrifugation protocol resulted in a ~2‐3‐fold enriched glycogen fraction from muscle samples for analysis. Total GLUT4 content was unaltered by exercise and we were unable to detect any GLUT4 in glycogen fractions, either with or without amylase treatment. In skinned muscle fiber segments, there was very little, if any, GLUT4 detected in wash solutions, except following exposure to 1% Triton X‐100. Amylase treatment of single fibers did not increase GLUT4 in the wash solution and there were no differences in GLUT4 content between fibers obtained before or after exercise for any of the wash treatments. Our results indicate no direct association between GLUT4 and glycogen in human skeletal muscle, before or after exercise, and suggest that alterations in GLUT4 translocation associated with exercise‐induced muscle glycogen depletion are mediated via other mechanisms. Abstract : There has been interest in whether there is a direct association between GLUT4 and glycogen in skeletal muscle. Using two different techniques we examined this question in human skeletal muscle. Our results suggest that no such association exists.